Development of a time-resolved fluorescence immunochromatographic strip for gB antibody detection of PRV - Suzhen Yang; Yaning Sun; Yunrui Xing; Lu Fan; Yongliang Li; Yanli Shang; Shujun Chai; Yunchao Liu (BMC Veterinary Research)
Abstract Background Pseudorabies (PR) is a highly contagious disease, and it causes significant economic losses to the global swine industry. Vaccination plays an important role in the prevention and control of pseudorabies virus (PRV). To evaluate vaccine efficacy, there is a need for a quick and straight forward method to monitor PRV-induced antibody levels in practice. Results A time-resolved fluorescence immunochromatographic (TRFIC) strip was developed for the serological detection of PRV gB antibodies in swine. Following systematic analysis and evaluation, the assay demonstrated a high degree of correlation with established reference method. The positive and negative coincidence rates between the TRFIC strip and ELISA were 96.8% and 94.2%, respectively. Furthermore, comprehensive analytical and comparative assessments revealed that the TRFIC strip exhibited no cross-reactivity with antibodies against other porcine pathogens. Conclusion Given its high specificity, sensitivity, and convenience, the TRFIC strip is suitable for on-site detection of PRV gB antibodies and can serve as a valuable tool for monitoring PRV immune status in animal populations.